2020
DOI: 10.3329/ajmbr.v6i2.48045
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance study of Silver barb (Barbonymus gonionotus) by replacing fishmeal with soybean meal in the diet

Abstract: Increasing demand, uncertain availability, and increasing cost for fishmeal (FM), fish nutritionists have been driven to find alternative sources of protein. The aim of this study was to evaluate the effects of substituting FM with soybean meal (SM) on growth performance of silver barb, Barbonymus gonionotus. Five diets were prepared 0%SM (100%FM), 25%SM (75%FM), 50%SM (50%FM), 75%SM (25%FM) and 100%SM (0%FM) by replacing FM with SM. B. gonionotus having initial length and weight of 8.62±0.9 cm and 8.80±3.11 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In this study, B. gonionotus showed better tolerance to the FSM and SM diets, which resulted that the FSM and SM could replace at 50% of FM without compromising body WG and SGR (%). Similar results also have been reported in the case of silver barb ( 27 ), sea bass ( 28 ), tilapia ( 29 ), and even in the crustacean, juvenile Pacific white shrimp ( 30 ) without negative effects on the growth following the partial replacement of FM by SM or FSM. Fish fed with the FSM 40 and SM 40 diets were recorded with significantly ( p < 0.05) lower weight gain and SGR.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, B. gonionotus showed better tolerance to the FSM and SM diets, which resulted that the FSM and SM could replace at 50% of FM without compromising body WG and SGR (%). Similar results also have been reported in the case of silver barb ( 27 ), sea bass ( 28 ), tilapia ( 29 ), and even in the crustacean, juvenile Pacific white shrimp ( 30 ) without negative effects on the growth following the partial replacement of FM by SM or FSM. Fish fed with the FSM 40 and SM 40 diets were recorded with significantly ( p < 0.05) lower weight gain and SGR.…”
Section: Discussionsupporting
confidence: 84%
“…The fly (L. sericata) maggot was considered one of the important animal that can be grown in the chicken manure medium (Ali Khan et al, 2012;Hwangbo et al, 2009). Studies have shown that maggot meal may be a very effective replacement for fish meal, which serves as an excellent source of protein for making fish feed for commercial or small-scale aquaculture (Jahan et al, 2020;Medard et al, 2018;Djissou et al, 2016;Aniebo et al, 2009). Different animal and fish species were used in experiments to determine the impact of using maggot meal instead of other types of protein (Xu et al, 2022;Khan et al, 2016;Makinde and John, 2015;Aniebo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to Siddhuraju and Becher (2003) [22] , the use of fish meal as the main source of protein in aquaculture feeds is responsible for the high cost of these feeds. Due to its availability as well as the fluctuations in its price on the market, research has been focused on other alternative sources of proteins of animal origin that are cheaper and not usable for human consumption (Jahan et al, 2020) [14] . Maggot meal is increasingly used because of its high biological value in breeding animals.…”
Section: Introductionmentioning
confidence: 99%